Prevalence of coronary risk factors: fisherman vs non-fisherman in Tumpat Kelantan - Norazmi A; Idris, M.N.; Osman Ali (Universiti Kebangsaan Malaysia, 2000)
A cross-sectional study was conducted amongst 223 subjects consisting of 176 fishermen and 51 non-fishermen in Tumpat Kelantan. The objective was to compare the prevalence of coronary heart disease (CHD) risk factors between them. Questionnaires were used to obtain the socio-economic status whilst clinical assessments were carried out to determine the nutritional and health status of the population. It was found that fishermen had lower socio- economic status as compared to non-fisherman. Prevalence of poverty among fishermen was 71.4% and 36.8% had no formal education. Three main coronary heart disease risk factors found to be high were smoking (76%), HDL-cholesterol < 35mg/dl (95.8%) and hypertension (28.8%). The prevalence of risk factors were higher among fishermen as compared to nonfisherman. Calories and nutrients intake were low in the two groups. Calorie and protein intake for fishermen were lower (p<0.05) compared to nonfishermen. The study showed that 46.6% fishermen had two CHD risk factors and 24.1% had three or more as compared to non-fishermen (33.3% and 33.3% respectively). Only 8.3% fishermen and 15.2% non fishermen did not have any risk factor. There was a significant difference (p<0.05) in number of risk factors according to age group. This study indicated that fishermen have a potential to develop coronary heart diseases thus preventive measures should be instituted as soon as possible in order to alleviate those problems.